Dynamic capabilities : Myth or real deal for sustaining competitive advantage - Sivusuo, Jaakko (Vaasan yliopisto, 2019)
Digitalization, technological development and globalization have changed the business world drastically over the last decade. Competition has become more and more intense and new competitors emerge on the markets faster than ever. Many frameworks for strategic management have lost their importance in turbulent markets. Winning the competition requires dynamic capabilities from the organization. This dissertation compile of multiple case studies, where six organizations are operating mostly in service industry. Most of the study organizations are operating in aviation industry, which is the focused market segment in this research. This dissertation is built around two main research questions. First research question defines the need and drivers for dynamic capabilities. There is a genuine need of dynamic capabilities for the organizations in this research. Change drivers are the same between the organizations even though they have different business models and operate in different industries. Actual dynamic capabilities are defined in the second research question from the case organizations point of view. As a result three concrete dynamic capabilities are found. These are service productisation process, the model of excellence and strategic partnership. Findings from this research contribute to the theory of dynamic capabilities with new models on actual dynamic capabilities. Results also yield new knowledge and perspective for service and aviation industries.

Digitalisaatio, teknologian kehitys ja globalisaatio ovat muuttaneet yritysmaailmaa rajusti viimeisen vuosikymmenen aikana. Monet strategisen johtamisen viitekehykset ovat menettäneet merkitystä turbulenttisessa liiketoimintaympäristössä. Kilpailussa pärjääminen vaatii organisaatiolta dynaamisia kyvykkyyksiä. Tämä monitapaustutkimus tarkastelee dynaamisia kyvykkyyksiä kuuden organisaation kautta, jotka toimivat palveluliiketoiminnan toimialalla. Tarkasteltava liiketoiminta-alue on ilmailuliiketoiminta, jossa suurin osa tutkimukseen osallistuvista organisaatioista toimii. Ensimmäisen tutkimuskysymyksen kautta määritetään tarve ja ajurit dynaamisiin kyvykkyyksiin. Tuloksista havaitaan, että dynaamisille kyvykkyyksille on aito tarve tutkimukseen osallistuvissa organisaatiossa. Tämä ilmenee jokaisessa organisaatiossa, vaikka ne toimivat eri liiketoiminta-aloilla erilaisilla businessmalleilla. Toisen tutkimuskysymyksen kautta määritetään konkreettisesti, mitä nämä dynaamiset kyvykkyydet ovat. Tutkimus antaa tuloksena kolme käytännön mallia dynaamisiksi kyvykkyyksiksi, jotka ovat palveluiden tuotteistus, strateginen kumppanuus sekä tutkimuksen kautta kehitetty model of excellence, huippuosaamismalli. Tutkimus tuo oman lisänsä dynaamisten kyvykkyyksien teoriaan käytännön menetelmien ja mallien muodossa. Tämä tutkimus antaa uutta näkökulmaa ja tuloksia palveluliiketoiminnan sekä ilmailuteollisuuden näkökulmasta, mutta tuloksia voidaan soveltaa myös muille toimialoille.
Keywords: jatkuva kilpailuetu; dynamic capabilities; competitive advantage; service business; dynaamiset kyvykkyydet; kilpailukyky; kilpailuetu; palveluliiketoiminta; fi=Tuotantotalous|en=Industrial Management|